Conciliation of Land Disputes in Vietnam: A Critical Analysis of Current Law and Practice with Recommendations for Reform - Nguyen Quang Tuyen; Nguyen Hai An; Nguyen Thi Huong; Hoang Nguyen Binh; Ngo Thi Thinh; Bui Thu Dung; Tran Thi Ha Thuong; Pham Thi Thuy Duong; Nguyen Quang Tuyen; Nguyen Hai An; Nguyen Thi Huong; Hoang Nguyen Binh; et al. (LUCK HOUSE GRAPHICS LTD)
This study proposes several specific amendments to the Land Law to clarify and improve the conciliation procedure and legal significance, including allowing the People’s Committee to enforce agreements following successful conciliations. Increased training and higher standards and remuneration for conciliators are also needed. Conciliation for citizen-state disputes should be studied as an alternative to the administrative complaint system. A community consultation mechanism for land acquisition and state-land management actions could also reduce disputes and instill a more cooperative attitude by all stakeholders.